2022
DOI: 10.3390/plants11020176
|View full text |Cite
|
Sign up to set email alerts
|

Continuous LED Lighting Enhances Yield and Nutritional Value of Four Genotypes of Brassicaceae Microgreens

Abstract: The effect of continuous lighting (CL, 24 h) and light spectrum on growth and nutritional quality of arugula (Eruca sativa), broccoli (Brassica oleracea var. italic), mizuna (Brassica rapa. var. nipposinica), and radish (Raphanus sativus var. radicula) were investigated in growth chambers under light-emitting diode (LED) and fluorescent lighting. Microgreens were grown under four combinations of two photoperiods (16 h and 24 h) providing daily light integral (DLI) of 15.6 and 23.3 mol m−2 day−1, correspondingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 69 publications
5
36
0
Order By: Relevance
“…nipposinica), and radish (Raphanus sativus var. radicula) in growth chambers [159]. The mild oxidative stress induced by continuous light treatment led to an increase in non-enzymatic antioxidants (anthocyanin, flavonoid, and proline) and enhanced the activities of antioxidant enzymes.…”
Section: Effects Of Light Intensity Exposure Time and Light Sourcesmentioning
confidence: 98%
See 1 more Smart Citation
“…nipposinica), and radish (Raphanus sativus var. radicula) in growth chambers [159]. The mild oxidative stress induced by continuous light treatment led to an increase in non-enzymatic antioxidants (anthocyanin, flavonoid, and proline) and enhanced the activities of antioxidant enzymes.…”
Section: Effects Of Light Intensity Exposure Time and Light Sourcesmentioning
confidence: 98%
“…The mild oxidative stress induced by continuous light treatment led to an increase in non-enzymatic antioxidants (anthocyanin, flavonoid, and proline) and enhanced the activities of antioxidant enzymes. As the effects were more pronounced under LED lighting, Shibaeva et al [159] concluded that one could produce microgreens of arugula, broccoli, mizuna, and radish under LED continuous light with economic and nutritional benefits.…”
Section: Effects Of Light Intensity Exposure Time and Light Sourcesmentioning
confidence: 99%
“…While this type of growing system can have very high yield per unit of land area, it is energy intensive. All the light required for plant growth and photosynthesis needs to come from artificial lighting with the use of electricity (Shibaeva et al, 2022b). Even if the adoption of the energy-efficient lightemitting diode (LED) fixtures can reduce the electricity use (van Delden et al, 2021), the electricity used by LED lighting still represents upwards of 20% of operating costs in plant factories; second only to labour (Kozai and Niu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…More recent research in these two crops have provided evidence that dynamic CL, which involves a change in light spectrum between daytime and nighttime, can result in injury-free production (Lanoue et al, 2019;Lanoue et al, 2022). Some cultivars of lettuces and some members of the Brassicaceae microgreen family have also been shown to have positive interactions with CL (Ohtake et al, 2018;Shibaeva et al, 2022b). Since the production period of microgreens is short, and CL-injury in tomatoes and peppers tends to take more than a month to have noticeable reductions in yield (Lanoue et al, 2021a), we hypothesize that CL may not compromise the production of microgreens and could be a viable production strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, each species requires studies to be performed for the selection of optimal light setting to maximize efficiency, yield, and nutritional quality of plants. Our previous research [10] has shown that arugula, mizuna, broccoli and radish arugula can tolerate continuous lighting during production period (11 days). These microgreens grown under continuous lighting (24 h photoperiod) had higher yield and robust index and increased nutritional value compared to 16 h photoperiod, as they accumulated more antioxidative phytochemicals (carotenoids, anthocyanins, flavonoids, proline, antioxidant enzymes).…”
Section: Introductionmentioning
confidence: 99%